Community-acquired Pseudomonas aeruginosa sepsis presenting with ecthyma gangrenosum in a neutropenic infant: a case report - Wang, Xing; Xiao, Yongmei; Ge, Ting; Zhang, Ting; Li, Xiaolu (Frontiers in Pediatrics, 2025)
BackgroundEcthyma gangrenosum (EG) is a distinctive cutaneous marker of Pseudomonas aeruginosa (P. aeruginosa) bacteremia, particularly in neutropenic hosts. In infants, community-acquired P. aeruginosa infection can precipitate fulminant septic shock with high mortality, underscoring the importance of early EG recognition.Case presentationWe report a 4-month-old ex-preterm girl presenting with fever, lethargy, and feeding intolerance. Investigations revealed profound neutropenia (ANC 0.08 × 109/L), markedly elevated inflammatory markers, and a violaceous perianal plaque. Within 24 h, the lesion progressed to necrotic ulceration with septic shock. Blood and wound cultures confirmed P. aeruginosa. Management included meropenem therapy, continuous renal replacement for cytokine storm, intravenous immunoglobulin, and urgent surgical debridement, resulting in clinical stabilization and wound improvement.ConclusionsEG is an early sentinel sign of community-acquired P. aeruginosa bacteremia in neutropenic infants. Careful perianal and genital examination is essential in febrile neutropenia, and prompt initiation of anti-pseudomonal therapy with timely source control is critical to reduce mortality.